Detection and Classification of Hydrolyzed Dairy Additives Using Electronic Noses - Vorobioff, Juan; Adaro, Mauricio Omar; Boggio, Norberto Gabriel; Magallanes, J.; Boselli, A.; Lamagna, Federico Agustín; Rinaldi, Carlos Alberto (American Scientific Publishers, 2018)
Fil: Vorobioff, Juan. Comisión Nacional de Energía Atómica; Argentina